Parental Stress Scale: Translation and Preliminary Testing for A Gujarati Sample - Manan J Patel; Prakash B Patel; R K Bansal (Medsci Publications, 2016)
Introduction: Parental Stress Scale is an 18 item self-report scale which represents positive (e.g. emotional benefits, personal development) and negative (demands on resources, restrictions) themes of parenthood. This study was aimed to translate English version of Parental Stress Scale into Gujarati and to do preliminary testing for reliability by a study conducted among medical professionals. Methods: English version of PPS was translated by two independent bilingual translators into Gujarati. It was back-translated into English by another two independent translators. The translated questionnaire was then gone through cognitive debriefing process, pilot testing and cultural adaptation process. This forward-backward process was repeated until satisfactory agreement was attained. Results: Mean scores of Gujarati and English version of parental stress scale were 34.14 ± 10.92 and 35.07 ± 10.83 respectively. There was no significant difference between these mean scores (p value 0.310). Reliability coefficients as measured by Cronbach's alpha for the Gujarati scale was calculated 0.924. Conclusion: High Cronbach's alpha co-efficient was found for the Gujarati version of Parental Stress Scale. We can therefore assert that it is a reliable tool for identifying parental stress. It can be used to show whether an intervention has had a positive effect on parental stress or not among native Gujarati person.